2016
DOI: 10.5812/ircmj.31146
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Coronary Artery Disease and Genetic Polymorphisms of Melanoma Inhibitory Activity 3

Abstract: BackgroundMelanoma Inhibitory Activity 3 regulates the plasma level of LDL cholesterol. The c.3169 + 315G > A single-nucleotide polymorphism of the MIA3 gene has been reported to be associated with serum coronary artery disease (CAD). However, there have been no studies analyzing the association of this polymorphism with CAD in Iranian individuals with CAD.ObjectivesTherefore, in the present study we have investigated the potential protective effect of the rs3008621 MIA3 polymorphism in 188 subjects with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(25 reference statements)
1
0
0
Order By: Relevance
“…It is reported that the mutation of family members reduces cholesterol and triglyceride levels in mice [31]. Another family member can regulate the plasma low-density lipoprotein-cholesterol concentration and is associated with coronary artery disease [32]. Our study found for the first time that CTAGE11P genetic variants are associated with FPI in the Chinese people.…”
Section: Figure 1 Manhattan Plot For Loci Associated With Fasting Pro...supporting
confidence: 56%
“…It is reported that the mutation of family members reduces cholesterol and triglyceride levels in mice [31]. Another family member can regulate the plasma low-density lipoprotein-cholesterol concentration and is associated with coronary artery disease [32]. Our study found for the first time that CTAGE11P genetic variants are associated with FPI in the Chinese people.…”
Section: Figure 1 Manhattan Plot For Loci Associated With Fasting Pro...supporting
confidence: 56%